Seed loss as a result of pod shatter in spring rape and spring turnip rape in Finland - Pahkala, Katri; Sankari, Hannele (MTT Agrifood Research Finland, 2001)
Tutkimuksen tarkoituksena oli määrittää ennen korjuuta varisevien kevätrypsin ja -rapsin siementen määrä. Varisemisen seuranta aloitettiin ennen optimikorjuupäivää ja sitä jatkettiin useita viikkoja sen jälkeen (myöhästetty korjuu). Tutkimuksessa määritettiin luonnollisen varisemisen seurauksena aiheutuneet satotappiot ja arvioitiin öljykasvien viljelyn aiheuttamaa rikkakasvipainetta viljelykierrossa. Rypsin ja rapsin varisemisherkkyys oli erilainen. Ennen tuleentumista ero kasvilajien välillä ei ollut merkityksellinen, mutta korjuun myöhästyessä rapsin variseminen lisääntyi selvästi rypsin varisemiseen verrattuna. Kasvuston varisemisen aiheuttama satotappio vaihteli vuosittain. Säätekijät kuten sademäärä ja tuulennopeus eivät kuitenkaan selvästi lisänneet varisemista.

The aims of this study were to evaluate seed shedding in spring turnip rape (Brassica rapa L.) and spring rape (B. napus L.) and to assess the effect of delayed harvesting on seed yield loss. Experiments on spring turnip rape (cv. Emma) were conducted in 1988-1990 and on spring rape (cv. Topas) in 1989-1990 in Jokioinen (60o49'N, 23o28'E). Rimmed tin boxes were used to collect seed from shattered pods. They were placed between the continuous rows before pods started to shatter. The shed seeds were collected two to three times a week. Susceptibility and timing of pod shattering varies between spring turnip rape and rape. However, before optimal harvest date spring rape does not shatter significantly more than spring turnip rape. Spring rape starts to shatter more compared with spring turnip rape after its optimal harvest date. It is also more sensitive to weather conditions than spring turnip rape. Furthermore, pod shattering after optimal harvest time differs among years. Weather conditions are discussed as one possible cause of pod shattering
Keywords: Ka; siementen variseminen; rypsi; rapsi; sää; sadonkorjuu; Brassica napus L.; Brassica rapa L.; delayed harvest; pod shattering; weather